Psychometric evaluation of the Diabetes Injection Device Experience Questionnaire (DID-EQ) and Diabetes Injection Device Preference Questionnaire (DID-PQ) - Louis S. Matza; Katie D. Stewart; Rosirene Paczkowski; Karin S. Coyne; Brooke Currie; Kristina S. Boye (SpringerOpen, 2018)
Abstract Background Previous research has examined patient perceptions of insulin injection devices. However, a range of injectable medications other than insulin are now used to treat type 2 diabetes. No patient-reported outcome (PRO) instruments have been developed taking into account the perceptions of patients using newer injection devices, which are often different from those used in the past. Therefore, the primary purpose of this study was to evaluate a new PRO instrument focusing on patients' experiences with injection devices, including those used for newer treatments such as GLP-1 receptor agonists. Methods Patients with T2D treated with non-insulin injectable medications were recruited via advertisements and six clinical sites in the US. All participants completed the draft Diabetes Injection Device - Experience Questionnaire (DID-EQ) and additional measures administered for validity assessment. Participants who had experience with two non-insulin injection devices also completed the draft Diabetes Injection Device - Preference Questionnaire (DID-PQ). Analyses focused on item reduction (item performance, exploratory factor analysis), reliability, and validity. Results One hundred fourty two patients (mean age = 63.0y; 56.3% female) participated. Item reduction yielded a 10-item version of the DID-EQ, including a 7-item Device Characteristics subscale and three global items assessing satisfaction, ease of use, and convenience of the injection device. The DID-EQ demonstrated good internal consistency reliability (Cronbach's alpha of Device Characteristics subscale = 0.80) and 7-day test-retest reliability (ICCs: 0.92 for Device Characteristics subscale; 0.65 to 0.91 for the three global items). Construct validity was demonstrated via correlations with previously validated instruments (e.g., correlations with the DTSQ treatment satisfaction subscale ranged from 0.56 to 0.60, all p < 0.0001; correlations with the TRIM-D Device ranged from 0.63 to 0.77, all p < 0.0001). Descriptive analyses of the DID-PQ were conducted with a subset of 27 participants who were able to use it to compare two devices. Conclusions This psychometric evaluation supports the reliability and validity of the DID-EQ, while providing initial information on the performance of the DID-PQ. These brief questionnaires complement measures of treatment efficacy and provide a more thorough picture of patients' experiences with non-insulin injectable treatments for type 2 diabetes.